Environmental surveillance of sporadic community-acquired cases of Legionnaires’ disease in Cordoba city (Spain), 2005-2010 - Rubio García, Ana; Gámez de la Hoz, Joaquín (Observatorio Medioambiental, 2014)
We examined the information of legionellosis surveillance system in the municipality of Cordoba (Spain) as a preventive resource for environmental health management and describes the public health implications of sporadic cases investigations. A multidisciplinary team analyzed information on surveillance of water sites potentially contaminated by Legionella and clinical data of the patients classified like community case; mapping patient’s home address using geographic information systems (GIS). Legionella pneumophila serogroup 1 was identified in 31 sporadic cases. 53 suspected sources, mainly cooling towers have been investigated. In no event is managed to locate infection source even if poorly maintained systems, structural deficiencies and operational failures were apparent. The use of GIS allowed us to identify two geographic areas where cases are concentrated within one radius of less than 500 meters. The finding of two suspected urban advised to reorient the preventive strategy in public health.